2011
DOI: 10.4049/jimmunol.1003292
|View full text |Cite
|
Sign up to set email alerts
|

Highly Activated Cytotoxic CD8 T Cells Express Protective IL-10 at the Peak of Coronavirus-Induced Encephalitis

Abstract: Acute viral encephalitis requires rapid pathogen elimination without significant bystander tissue damage. In this article, we show that IL-10, a potent anti-inflammatory cytokine, is produced transiently at the peak of infection by CD8 T cells in the brains of coronavirus-infected mice. IL-10+CD8 and IL-10−CD8 T cells interconvert during acute disease, possibly based on recent Ag exposure. Strikingly, IL-10+CD8 T cells were more highly activated and cytolytic than IL-10−CD8 T cells, expressing greater levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 43 publications
9
159
0
Order By: Relevance
“…A subset of effector CD8 + T cells secretes both IFN-γ and IL-10 and is thought to be involved in controlling tissue inflammation during infection. This subset has previously been identified in a mouse model for acute influenza virus [9], and in the brain of coronavirus-infected mice [10]. In humans, a regulatory CD8 + T cell subset generated in vitro from CD8 + CD28 − but not from CD8 + CD28 + T cells was able to inhibit T-cell proliferation and cytotoxicity by secretion of IL-10 [11].…”
Section: Introductionmentioning
confidence: 87%
“…A subset of effector CD8 + T cells secretes both IFN-γ and IL-10 and is thought to be involved in controlling tissue inflammation during infection. This subset has previously been identified in a mouse model for acute influenza virus [9], and in the brain of coronavirus-infected mice [10]. In humans, a regulatory CD8 + T cell subset generated in vitro from CD8 + CD28 − but not from CD8 + CD28 + T cells was able to inhibit T-cell proliferation and cytotoxicity by secretion of IL-10 [11].…”
Section: Introductionmentioning
confidence: 87%
“…Recent findings demonstrated that highly lytic CNS-derived CD8 T cells during JHMV infection are marked by IL-10 expression (Trandem et al, 2011). Surprisingly, IL-10 transcripts were decreased by N50% in IL-21R −/− relative to WT CD8 T cells at day 7 p.i., and~65% by day 10 p.i.…”
Section: Expression Of T Cell Effector Molecules Is Compromised In Thmentioning
confidence: 96%
“…For instance, the absence of IL-10 during influenza virus infection can lead on one hand to improved survival, due to enhanced T cell 17 and antibody responses 101 , or on the other, to exacerbated inflammation and immunopathology, leading to increased mortality 102 . Similarly, ablating IL-10 has been found to enhance protection against WNV 103 and vaccinia virus 104 , but to lead to increased pathology upon infection with RSV 105 , and death upon infection with mouse hepatitis virus 106 and corona virus 107 . Finally, as well as producing IL-10 themselves, effector CD4 + T cells can also promote IL-10 production by effector CD8 + T cells during virus infection 108 .…”
Section: Immunoregulation By Effector Cd4+ T Cellsmentioning
confidence: 99%